Single-phase shunt active filter with digital control - Pinto, J. G. (2007)
This paper presents a single-phase shunt active filter designed to minimize problems related to power quality in electrical systems. The power stage of the active filter is based on a two-leg full-bridge inverter, with a single capacitor in the dc side, and a filter inductor in the ac side. The control system is based on the instantaneous power theory in the α-β-0 reference frame (pq-theory), derived to be applied in single-phase systems. In essence, the shunt active filter is designed to drain, from the electric grid, harmonic and reactive components of the load currents, such that the system current will become, basically, a sinusoidal waveform, with low harmonic distortion, and in phase with the system voltage. Simulation results of the shunt active filter operating with three different loads are presented in order to verify its performance.